Energy monitoring and verification control interface for split unit air conditioners - Cronjé, Estienne; N.Jiya, Immanuel; Gouws, Rupert (International Journal of Engineering and Technology, 2019)
The aim of this paper is to present a new energy monitoring and verification control interface for the Eskom demand market participation (DMP) program that can be implemented on a commercial scale on all the split unit air conditioner systems of consumers actively participating in the program. After the detailed design was completed, the sub-system circuits were created and tested, and evaluation commenced. The sub-systems were integrated after each test and evaluation phase to see whether the system functionality performed as it should have. The final integration was implemented and the final system (consisting of a master – and slave controller unit) were placed inside their enclosures. From there on, the programming logic was modified to and the program was evaluated to see if the completely integrated system was still functional. The slave controller unit was attached to the split unit air conditioner together with the appropriate sensors to monitor and verify the operation of the air conditioner. The developed system was able to successfully monitor the current state of the split unit air conditioner, control it to a specific mode (usually fan mode) according to the required demand at that stage, verify that it has indeed been switched to that specific mode and provide an estimate of the power consumption in the current mode.